Persepsi Masyarakat Islam Terhadap Idea Penjanaan Dana Masjid: Kajian di Perak (Sains Humanika, 2014)
The mosque is a highly respected institution by Muslim society. Hence, a mosque is not only a place of worship for prayers or religious speech delivery, but the Muslim society regard this institution as the place to increase monetary and spiritual holy deeds through contributions in the form of waqf, sadaqah and others. Due to the fact that those contributions are continuous and potentially increase from time to time, it is important to determine the extent of agreement among Muslim society in Perak particularly towards generating the mosque fund for the purpose of wider benefits. Therefore, this study employs questionnaires distributed to mosque members in Perak to identify factor influences the Muslim society perception towards the idea of expanding the mosque fund by using the logistic regression method. The regression result indicates that factors of financial management, involvement as committee and education level are significant towards this idea. Thus, this study importantly implicates the need to enhance the mosque financial management and deliver the importance of this generating mosque activity to Muslim society for their benefit.Â
Keywords: Mosque institution; illiquid saving; fund generation; logistic model